Tilting stability analysis and experiment of the 3-DOF lifting platform for hilly orchards - Duan, Zhenhua; Qiu, Wei; Ding, Weimin; Liu, Yande; Ouyang, Yuping; Huang, Liang (International Journal of Agricultural and Biological Engineering, 2018)
An orchard-lifting platform is a type of mechanical equipment to assist growers in fruit picking, fruit tree pruning, flower thinning, and other operations. In its operational processes, the tilting stability directly affects the operational safety and adaptability under complex terrain conditions, while critical tilting angle is an important criterion to evaluate the tilting stability. Based on the structure and the operating characteristics of the three degree of freedom (3-DOF ) lifting platform for hilly orchards, the tilting stability was analyzed in different parked states, and the theoretical expressions of critical tilting angle were obtained; in the theoretical expressions, the influencing factors on tilting stability were determined as the parked position β1, the manned worktable rotary position β2, the lifting height h, and the load m. Based on the multi-body dynamics principle, the tilting stability simulation was carried out. The relative error of tilting angles was approximately 4.6% between simulation and tilting verification experiment, which indicated that the results of tilting stability simulation were reliable. Therefore, the multi-body dynamics simulation was used for further clarifying the influencing factors on tilting stability. A virtual orthogonal test was designed, and the results showed that critical tilting angle ranged from 20° to 44° when the factors were at different values, which indicated that the 3-DOF lifting platform for hilly orchards had a high tilting stability performance and could adapt to the operating conditions of hills with slope angles from 5° to 20°. The results of the range analysis and ANOVA showed that the influence intensity of factors on tilting stability was β1 > h > m > β2; at the same time, β1, h, and m exerted significant effect on tilting stability. The tilting stability first decreased and then either increased or decreased with the increasing lifting height; it gradually decreased with the increasing load. It also showed that the position of the manned worktable along the slope down always had the lowest tilting stability. This research can provide a theoretical basis and reference for the analysis of tilting stability of the lifting machinery for hilly orchards. Keywords: orchard-lifting platform, hills areas, tiling stability, influencing factors, analysis and experiment DOI: 10.25165/j.ijabe.20181106.3523 Citation: Duan Z H, Qiu W, Ding W M, Liu Y D, Ouyang Y P, et al. Tilting stability analysis and experiment of the 3-DOF lifting platform for hilly orchards. Int J Agric & Biol Eng, 2018; 11(6): 73–80.